Spacetime connectomics for describing and modelling complex dynamics of human brain states - Vohryzek, J (2021)
The human brain is poised to maintain reproducible behaviours while simultaneously allowing for flexible adaptability. Such characteristics are realised in complex systems endowed with metastable dynamics. The central tenet of this Thesis is to investigate rich and spontaneous brain dynamics in terms of their spatial and temporal properties in different brain states, namely the psychedelics induced and depressive state.